2018
DOI: 10.1101/329730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The high turnover of ribosome-associated transcripts fromde novoORFs produces gene-like characteristics available forde novogene emergence in wild yeast populations

Abstract: Little is known about the rate of emergence of genes de novo, how they spread in populations and what their initial properties are. We examined wild Saccharomyces paradoxus populations to characterize the diversity and turnover of intergenic ORFs over short evolutionary time-scales. We identified ~34,000 intergenic ORFs per individual genome for a total of ~64,000 orthogroups, which resulted from an estimated turnover rate relatively smaller than the rate of gene duplication in yeast. Hundreds of intergenic OR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 79 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…For many of these, ancestral ORFs were identified but were not expressed. Highlighting the differences between inter- and intra-species comparisons, a study in natural Saccharomyces paradoxus populations found that the number of de novo polypeptides identified more than doubled when considering intra-species diversity [73]. In primates, one early study identified 270 orphan genes (unique to humans, chimpanzees, and macaques), of which 15 were thought to have originated de novo [44], while a later report identified 60 de novo genes in humans alone that are supported by transcriptional and proteomic evidence [66].…”
Section: Prevalence Of De Novo Gene Birthmentioning
confidence: 99%
See 4 more Smart Citations
“…For many of these, ancestral ORFs were identified but were not expressed. Highlighting the differences between inter- and intra-species comparisons, a study in natural Saccharomyces paradoxus populations found that the number of de novo polypeptides identified more than doubled when considering intra-species diversity [73]. In primates, one early study identified 270 orphan genes (unique to humans, chimpanzees, and macaques), of which 15 were thought to have originated de novo [44], while a later report identified 60 de novo genes in humans alone that are supported by transcriptional and proteomic evidence [66].…”
Section: Prevalence Of De Novo Gene Birthmentioning
confidence: 99%
“…It is notable that even after application of this stringent pipeline, the 152 validated de novo genes that remained still represents a significant fraction of the mouse genome likely to have originated de novo . Generally speaking, however, it remains debated whether duplication and divergence or de novo gene birth represent the dominant mechanism for the emergence of new genes [63, 65, 73, 7577], in part due to the fact that de novo genes are likely both to emerge and to be lost more frequently than other young genes (see below).…”
Section: Prevalence Of De Novo Gene Birthmentioning
confidence: 99%
See 3 more Smart Citations